Airway Gene Expression Correlates of Respiratory Syncytial Virus Disease Severity and Microbiome Composition in Infants. (14th September 2020) - Chu, Chin-Yi; Qiu, Xing; McCall, Matthew N; Wang, Lu; Corbett, Anthony; Holden-Wiltse, Jeanne; Slaunwhite, Christopher; Grier, Alex; Gill, Steven R; Pryhuber, Gloria S; Falsey, Ann R; Topham, David J; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is the leading cause of severe respiratory disease in infants. The causes and correlates of severe illness in the majority of infants are poorly defined. Methods: We recruited a cohort of RSV-infected infants and simultaneously assayed the molecular status of their airways and the presence of airway microbiota. We used rigorous statistical approaches to identify gene expression patterns associated with disease severity and microbiota composition, separately and in combination. Results: We measured comprehensive airway gene expression patterns in 106 infants with primary RSV infection. We identified an airway gene expression signature of severe illness dominated by excessive chemokine expression. We also found an association between Haemophilus influenzae, disease severity, and airway lymphocyte accumulation. Exploring the time of onset of clinical symptoms revealed acute activation of interferon signaling following RSV infection in infants with mild or moderate illness, which was absent in subjects with severe illness. Conclusion s: Our data reveal that airway gene expression patterns distinguish mild/moderate from severe illness. Furthermore, our data identify biomarkers that may be therapeutic targets or useful for measuring efficacy of intervention responses. Abstract : Our data suggest that acute, interferon-mediated intracellular signaling in airway cells is critical for normal responses to RSV infection in infants.